PERBANDINGAN FIDIC DENGAN UNDANG-UNDANG JASA KONSTRUKSI INDONESIA TERKAIT KONTRAK MASS RAPID TRANSIT UNDERGROUND CP 106 - ANNISA MAYANGSARI (2020)
This research was conducted to understand the compare contained therein in FIDIC Design and Build Contract Conditions with Contract Conditions based on Construction Service law Number 2 of 2017 where the contract is seen as a law that must be fulfilled and regulates the rights and obligations of control between the Service User and Service Provider in the Project. In the world of construction in Indonesia, standards are used for contract documents based on Construction Service law Number 2 of 2017 about construction. while construction in Indonesia where the implementation of the Project is funded by Foreign Loans using International Contract standards or known as FIDIC (Federation Internationale Des Ingenieurs Conceils) and has been widely used by many countries. The analysis conducted is to compare between standard and FIDIC procedures Construction Service law Number 2 of 2017 about construction. The purpose of this comparison is to identify the compare between the two documents, then evaluate the results of the comparison found. The results of the comparative analysis that the Contract Conditions based on Fidic are considered more effective and clear according to the objectives of the construction project and cover broad aspects compared to the Contract Conditions based on Indonesia Constitution Number 2 of 2017 about construction. The FIDIC standard provides more certainty and clear and detailed provisions relating to Variation Procedures (Work Plus Less) and Late Payment Payments from Service Users to Service Providers. Keywords: Contract, FIDIC, UUJK No 2 of 2017